A case report on peritoneal inclusion cyst with entrapped ovary and an endometriotic cyst causing diagnostic dilemma - Stumpf, Luciana; Zinzuwadia, Shuchi; Ploussard, Brett; Zinzuwadia, Shweta; Bhrahmbhatt, Elizabeth; Adam, Kailynn; Jawahar, Anugayathri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Peritoneal inclusion cysts (PIC) occur most frequently when abdominal adhesions attach to an ovary. These adhesions are commonly seen in patients with a history of abdominal surgery. Physiologic fluid following ovulation that would normally be absorbed by the peritoneum gets entrapped within these adhesions. Women most frequently complain of back pain or pelvic pain when peritoneal inclusion cysts are present. We present a patient with prior surgical history who presented with suprapubic pain and was found to have a complex cyst on imaging. Gynecologic oncology was consulted due to its complex imaging appearance and large size and was ultimately resected despite negative tumor markers. We present our case with pathologic correlation of imaging findings to emphasize this benign entity with no malignant potential. A confident imaging diagnosis in correlation with laboratory markers can help prevent aggressive surgical management.